2014
DOI: 10.1186/bcr3606
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutations, phosphatase and tensin homolog, human epidermal growth factor receptor 2, and insulin-like growth factor 1 receptor and adjuvant tamoxifen resistance in postmenopausal breast cancer patients

Abstract: IntroductionInhibitors of the phosphatidylinositol-3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway can overcome endocrine resistance in estrogen receptor (ER) α-positive breast cancer, but companion diagnostics indicating PI3K/AKT/mTOR activation and consequently endocrine resistance are lacking. PIK3CA mutations frequently occur in ERα-positive breast cancer and result in PI3K/AKT/mTOR activation in vitro. Nevertheless, the prognostic and treatment-predictive value of these mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
66
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 48 publications
(71 reference statements)
14
66
0
1
Order By: Relevance
“…Alterations in the PI3K/AKT pathway, mainly PIK3CA mutations, have been shown most frequent in the luminal subtypes, suggesting a crosstalk between ER and PI3K/AKT [3]. Aberrant PI3K/AKT signalling has been connected to poor response to anti-oestrogen therapies in several studies [20,[42][43][44][45][46][47][48][49][50]. In the present study, we showed PTPN2 gene loss as a new potential marker of endocrine resistance.…”
Section: Discussionsupporting
confidence: 62%
“…Alterations in the PI3K/AKT pathway, mainly PIK3CA mutations, have been shown most frequent in the luminal subtypes, suggesting a crosstalk between ER and PI3K/AKT [3]. Aberrant PI3K/AKT signalling has been connected to poor response to anti-oestrogen therapies in several studies [20,[42][43][44][45][46][47][48][49][50]. In the present study, we showed PTPN2 gene loss as a new potential marker of endocrine resistance.…”
Section: Discussionsupporting
confidence: 62%
“…Our PIK3CA mutation rate (23.3%) was consistent with the literature, as well as our rate of different hotspot mutations [3,14,19,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Also, we confirmed significant associations of different types of PIK3CA mutations with clinicopathological and molecular characteristics.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, PIK3CA mutations do not seem to have Notably, PTEN loss and PIK3CA mutations are regarded in the literature to be the most frequent downstream molecular aberrations affecting PI3K-AKT signaling, nevertheless only a minority of studies has examined the possible role of such combined effect [26,31,33,34]. Interestingly, each one of these studies provided different results, which may be attributed to the diverse population characteristics and treatments applied, for example only HER2 positive [33], only postmenopausal [26,31], or only hormone receptor positive cases [34]. Also, the differences in the methodologies and/or cutoffs used in assessing PTEN protein expression may have further influenced the results as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…104 However, constitutive activation of PI3K does not seem to confer this resistant phenotype. [105][106][107] Despite the lack of a correlation between response to anti-estrogen therapy and PI3K alterations, there is preclinical evidence pointing to the benefit of a combination of inhibitors of ER and the PI3K pathway. 108,109 In fact, we have reported that PI3K pathway inhibition upregulates ER transcriptional activity and increases cell survival dependency on ER, which translates into a synergism between PI3K inhibitors and ER degraders with increased tumor control.…”
Section: Combinations Of Pi3k Inhibitors With Endocrine Therapymentioning
confidence: 99%